Meningkatkan Perkembangan Fisik Motorik Aud Dengan Bahan Alam Melalui Metode Meronce Biji Bidara Di Ram 112 Miftahul Ulum Sooko - Putri Ayu Indah Lutfiah; Naning Yuliani (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Being creative in developing various media in order to improve children's motor skills is one of the mandatory skills that teachers must have. From birth to the age of six children will develop through educational stimuli that help the growth of children's physical and spiritual development so that children are ready to follow the next level of education .Meronce is a fun thing that can be done by children. With meronce children will assemble from an object into a new work. One example is grinding the seeds of bidara. And the results of meronce bidara can be in the form of necklaces, bracelets or beads. The purpose of this study was to find out how to inculcate aspects of Physical Motoric development in children aged 4-5 years at RAM 112 Miftahul Ulum Sooko. The method used is a qualitative method with a descriptive approach utilizing natural materials around us. The results of this study can be concluded that singing skills can improve children's motoric development in the form of small muscles and train the strength and skills of the use of children's fingers. By grinding these bidara seeds, they can hone children's creativity and imagination in their work. So that children can learn in a fun way and add insight into the natural materials around them